Developing Higher Order Thinking Skills Through LMS in History Classes Case Study Master two Students - ABBOU, Imane; ALLAOUI ,Soumia; Gasmi,MUSTAPHA (University of Ammar Theledji -Laghouat, 2020)
The current work endeavors to explore teachers and students’ attitudes towards Learning management system, critical thinking skill, and more importantly, towards developing critical thinking skill through LMS in history teaching and learning at the department of letters and English Language at Amar thlidji Lghouat University. The main problem is that students find the memorization of dates, names and historical facts too difficult that may hinder their learning process and development. Therefore, these innovative teaching strategies and tools can help students to understand and recall the information easily and enable them to think critically. In order to carry on this research, a descriptive and analytical study has been conducted. Two different questionnaires were administrated to eight master two students and three teachers of different modules as a method of collecting data. The findings revealed that both teachers and students are aware of the need to develop critical thinking skills and stress the importance of LMS. Following the research findings, it is highly recommended to raise teachers and students’ awareness about the importance of these teaching tools as well as critical thinking skills in foreign language teaching and learning that can help learners enhance their critical thinking not only in history but in all classes